Bipolar Electrochemical Approach with a Thin Layer of Supporting Electrolyte towards the Growth of Self‐Organizing TiO2 Nanotubes. Issue 3 (2nd February 2016) - Saqib, Muhammad; Lai, Jianping; Zhao, Jianming; Li, Suping; Xu, Guobao
Abstract: The front cover artwork is provided by the group of Prof. Guobao Xu at State Key Laboratory of Electroanalytical Chemistry, Changchun Institute of Applied Chemistry, Chinese Academy of Sciences (http://people.gucas.ac.cn/∼guobaoxu?language=en ). The image shows the bipolar electrochemical approach with a thin layer of supporting electrolyte towards the growth of self‐organizing TiO2 nanotubes in a horizontal direction for single and multiple samples in a single wireless run with tunable diameters. Read the full text of the Communication at10.1002/celc.201500182 . Abstract : "Porous metal‐oxide films have attracted huge scientific interest, owing to their unique electronic properties and highly promising applications in the fields of dye‐sensitized solar cells, water splitting, photocatalysis, biomedical devices, and so on. A facile and environmentally friendly wireless strategy to grow self‐organizing TiO2 nanotubes in a horizontal direction by utilizing a thin layer of electrolyte is developed. The strategy enables high‐throughput production of porous metal‐oxide films in a single wireless run…." Find out more about the story behind the front cover research at10.1002/celc.201500182 .